2019
DOI: 10.1111/1750-3841.14918
|View full text |Cite
|
Sign up to set email alerts
|

Pesticides (Hexachlorocyclohexane, Aldrin, and Malathion) Residues in Home‐Grown Eggs: Prevalence, Distribution, and Effect of Storage and Heat Treatments

Abstract: The abuse of pesticides in home gardens may lead to contamination of home-grown eggs. This study aimed to determine the prevalence of hexachlorocyclohexane (HCH), aldrin, and malathion pesticides residues in egg white and egg yolk of home-grown eggs in Jordan; and the effect of refrigerated storage and heat treatment (boiling and frying) on residues level. High-performance liquid chromatography was used to detect pesticide residues in egg samples (n = 200) obtained from households that raise laying hens in Jor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…In general, both research toxicity studies and pesticide registration protocols focus on assessing the effects of isolated active substances, while the effects of combined compounds are only assessed when those are part of the same formulation. However, the simultaneous application of two or more pesticides in the same agricultural area is a common event during the same cropping season. , Hence, a complex cocktail of agrochemicals, which are not coformulated as single products, can be simultaneously detected in food and water samples. …”
Section: Discussionmentioning
confidence: 99%
“…In general, both research toxicity studies and pesticide registration protocols focus on assessing the effects of isolated active substances, while the effects of combined compounds are only assessed when those are part of the same formulation. However, the simultaneous application of two or more pesticides in the same agricultural area is a common event during the same cropping season. , Hence, a complex cocktail of agrochemicals, which are not coformulated as single products, can be simultaneously detected in food and water samples. …”
Section: Discussionmentioning
confidence: 99%
“…A study was conducted on the home produced eggs in Jordan revealed that are highly contaminated with pesticide residues particularly Malathion (44%) and Aldrin (33%), at an unacceptable high limits and form potential harmful to the consumer (Alaboudi et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The identification and concentrations of the questioned pesticides (endosulfan, heptachlor, malathion, chlorpyrifos, bifenthrin, deltamethrin, and fenoxycarb) were analyzed using liquid chromatography with tandem mass spectrometry (LC-MS/MS) as per United States Department of Agriculture Food Safety and Inspection Service, Office of Public Health Science (2018) and as previously described (Alaboudi et al, 2019).…”
Section: Pesticides Quantitationmentioning
confidence: 99%